(untitled) (Eurasian Research Bulletin, 2023)
The article discusses data on the solubilization of heavy metals in the liver of cattle in the form of aqueous extracts and ensuring the complete separation of heavy metals in the liver, the determination of the amount of mercury, cadmium, lead and iron in the liver of cattle by the method of potentiometric oximetric titration on the device "Ionomer U- 130" and spectrophotometric determinations were carried out on the "Spectrophotometer KFK-3".